Viruses Causing Aseptic Meningitis: A Tertiary Medical Center Experience With a Multiplex PCR Assay - Aldriweesh, Mohammed A.; Shafaay, Edi A.; Alwatban, Saud M.; Alkethami, Obeid M.; Aljuraisi, Faisal N.; Bosaeed, Mohammad; Alharbi, Naif Khalaf (Frontiers in Neurology, 2020)
Background: CNS infection is associated with high rates of morbidity and mortality, and despite advancements in molecular testing, aseptic meningitis remains challenging to diagnose. Aseptic meningitis cases are often underreported worldwide, which impacts the quality of patient care. Therefore, we aimed to assess the results of BioFire® FilmArray® Meningitis/Encephalitis (ME) PCR Panel, clinical characteristics, and etiologies of aseptic meningitis patients. Methods: From January 2018 to January 2020, all pediatric and adult patients in a large tertiary medical center who underwent lumbar puncture, CSF testing by a ME multiplex PCR panel, and who fit the aseptic meningitis definition were retrospectively reviewed. Results: Data were reviewed from 1,607 patients; 240 met the inclusion criteria (54.6% males; 68.8% <4 years of age). The rate of detected viral causes of aseptic meningitis was 40.4%; therefore, 59.6% of the patients remained with unidentified etiology. Among the identified viral meningitis, enterovirus and HHV-6 were the most common (25% and 7.9%, respectively). The median length of hospital stay was six days, and it was longer in patients with unidentifiable aseptic meningitis (p ˂ 0.0001). Conclusion: Aseptic meningitis is common among suspected meningitis patients, although most cases remained of unknown etiology. The most common identified viruses were enterovirus followed by HHV-6; and predominance in males and the pediatric age group. These results highlight that further research is needed to identify other etiologies and possible additional viral pathogens for aseptic meningitis in the current diagnostic methods.